2021
DOI: 10.1002/rmv.2226
|View full text |Cite
|
Sign up to set email alerts
|

Covid‐19 and oral diseases: Crosstalk, synergy or association?

Abstract: Summary The coronavirus disease 2019 (Covid‐19) is a viral infection caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) that clinically affects multiple organs of the human body. Cells in the oral cavity express viral entry receptor angiotensin‐converting enzyme 2 that allows viral replication and may cause tissue inflammation and destruction. Recent studies have reported that Covid‐19 patients present oral manifestations with multiple clinical aspects. In this review, we aim to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0
19

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(121 citation statements)
references
References 125 publications
2
100
0
19
Order By: Relevance
“…One interesting possibility is the desmoglein (DSG) family, and DSG1 and 3 are found in the autoimmune blistering pemphigus disorders. While oral ulceration and blistering has been described in COVID-19 (16,17)) it is by no means a commonly reported feature in large clinical studies such as ISARIC4C (Coronavirus Clinical Characterisation Consortium) (18).…”
Section: Discussionmentioning
confidence: 99%
“…One interesting possibility is the desmoglein (DSG) family, and DSG1 and 3 are found in the autoimmune blistering pemphigus disorders. While oral ulceration and blistering has been described in COVID-19 (16,17)) it is by no means a commonly reported feature in large clinical studies such as ISARIC4C (Coronavirus Clinical Characterisation Consortium) (18).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies had shown that SARS-CoV-2 infection is a risk factor for ageusia. There are case reports of COVID-19 being associated with necrotizing periodontal disease, oral ulcers, blisters, salivary gland alterations, white and erythematous plaques, and recurrent herpetic lesions [ 42 – 44 ]. The suggested pathways for these COVID-19 related oral lesions was mediation by SARS-CoV-2-associated tropism of endothelial cells and COVID-19-mediated endothelitis that promotes inflammation of oral tissues [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous oral lesions have been reported in patients with COVID-19 (3)(4)(5)(6)(7)(8). These manifestations include a wide and varied range, from the inflammation of the papillae of Wharton's duct to plaques on the tongue; however, the exact relationship between many of these lesions and pathologic processes of the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection is still a subject of investigation (9). Some of these lesions can clearly be attributed to causes other than the direct effects of SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%